DETERMINING OF PERMEABLE ZONE NEAR SURFACE THROUGH THE ANALYSIS OF GAS MERCURY, RADON AND THORON CONCENTRATION IN THE NORTH WAYANG-WINDU GEOTHERMAL FIELD - APRILLIA (NIM : 12113023), PUTRI
Geothermal energy is present as one of the alternative energy to fulfill the energy that human needed. One method of geothermal exploration that has proven to be inexpensive and effective in conducting preliminary exploration is by measuring mercury concentration. Determination of permeable zone is the first step to find source of reservoir geothermal. One g the method to deliniate permeable zone are measuring the mercury, radon and thoron gas in the field. The study was conducted on nine measurement points in the northern Wayang-Windu geothermal field from October 2016 until June 2017. Mercury gas concentrations were measured from shallow drill holes made at depths of 3 to 5 meters. Measurements are made within 3 to 4 weeks interval of 5 cycles. Measurements were made using an EMP Gold Anayser tool that measures the concentration of mercury gas by the principle of amalgam by absorbing Hg using Au. But the other parameter did not show any correlations. The measured mercury gas concentration has a value of 0.01 ng / m3 up to 16.88 ng / m3. High mercury gas concentrations are present at points K05, K08 and K13. The measured mercury gas concentration has a value of 1 ng / m3 up to 16.88 ng / m3. High mercury gas concentrations are present at points K05, K08 and K13. The consentration mercury value are overlay with geological conditions including surface fault, sub surface fault, topography, lithology, lineament, manifestation, radon concentration, radon/thoron concentration ratio. The mercury concentration values have correlation with the manifestations, radon concentration and radon/mercury concentration ratio. Radon and thoron concentration is used with mercury to deliniate permeabel zone. High mercury values are in the manifestation area but in this area indicate low radon and thoron gas concentration. From the results of the analysis, it is suspected that there are two major permeabity zones with NE-SW trending in the north and minor NE-SW permeability zone in the south. The value of ratio radon/thoron gas indicate that the source of geothermal is depth. The major permeability zones have a high permeability rate which is likely to have high porosity and fracture rocks.